The Current Trends of Globalization in Georgia - Khorguashvili, Tea; Khorguashvili, Natia (European Journal of Sustainable Development, 2016)
The work is devoted to a very important and topical issue at present – integration of Georgia in the conditions of globalization and the role of foreign investment in the economic development of the country. The development of the processes of globalization and the international movement of capital produced the largest volume of foreign investments, especially in developing countries. Like all events, foreign investments has advantages and disadvantages, which are shown in this paper. Also there is analyzed globalization and the index of economic freedom of Georgia and the implementation scales of foreign investments on the example of 2015. Today the issue of globalization has been enterered more in our lives which in itself means to search for the joint ways to solve the problems which are raised in front of the countries of the world. Modern globalization has embraced all spheres of the existence of the society. For globalization it is characteristic exchange of national and international relations which caused the integration of the countries of the world under the overall economic, political and social systems. The long-term result of globalization is the formation of the global economy, which is based on the relations without barriers between the national economies. The role of economic relations of the country grows in the process of globalization. Taking into account the globalization processes for the country's economic development is particularly important for those states such as Georgia. Georgia is obliged to take into account the general regularities of the globalization of the world and to engage in the processes of the international integration.